ELECTION VIOLATION AND ELECTION LAW ENFORCEMENT IN GENERAL ELECTION IN INDONESIA - Prawira, Syailendra Anantya (Jurnal Hukum Volkgeist, 2019)
General Elections are the embodiments of the mandate stipulated in the 1945 Constitution of the Republic of Indonesia Article 1 paragraph (2) which affirms that "sovereignty is in the hands of the people and carried out according to the Constitution". The Formulation Document that will be formulated in the research are: (1) What is the violation in the general election? And (2) What is law enforcement in general election. The method used in this study is normative legal research, normative legal research methods or library law research methods are methods or procedures that are used in legal research by examining existing library material. Election violations constitute acts prohibited by the Election Law against election organizers resulting in the imposition of sanctions for violations. The enactment of Law Number 7 Year 2017 on General Elections provides for different types of violations, disputes, criminal offenses and electoral disputes. The crime of elections is a criminal offense punishable by a particular punishment based on the criminal justice system. The purpose of election is to carry out popular sovereignty and the realization of the political rights of the people to produce leaders who will occupy important positions in the government.